Comparison of the Principle of Meaningful Participation in the Process of Law Formation in Indonesia, Switzerland, and Sweden - Saragih, Geofani Milthree; Putra, Rengga Kusuma; Ishwara , Ade Sathya Sanathana; Nugroho, Aziz Widhi; Ivory, Jared (JUSTISI, 2025)
This study aims to analyze the effectiveness of applying the principle of meaningful participation in lawmaking in Indonesia, Switzerland, and Sweden The method used is normative juridical with a case study and comparative law approach. Data collection was conducted through a literature review of regulations, official documents, and related literature, which was then analyzed qualitatively using a descriptive-comparative framework. The novelty of this research lies in its functional comparative approach, which not only compares legal frameworks but also the practical implementation of the principle of participation in the legislative processes of each country. This study highlights the gap between formal regulations and substantive practices in Indonesia, and identifies best practices from Swiss referendum democracy and Swedish public consultation mechanisms. The results show that Indonesia still faces challenges in ensuring substantive public participation, which tends to be formal and limited without influencing the substance of regulations. In contrast, Switzerland implements direct democracy through referendums, and Sweden has developed transparent and structured public consultation mechanisms. However, the future prospects in Indonesia are quite positive, with increasing demands for transparency, technological advances, and the role of civil society opening up opportunities to develop more inclusive and effective public participation in law-making. In conclusion, although Indonesia is still limited in ensuring substantial public participation, the opportunities to improve participation mechanisms through transparency and technology are quite promising, leading to a more inclusive and influential system in law formation.